2017
DOI: 10.1175/jas-d-16-0075.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Processes Leading to the Rapid Intensification of Typhoon Megi (2010)

Abstract: The processes leading to the rapid intensification (RI) of Typhoon Megi (2010) are explored with a convection-permitting full-physics model and a sensitivity experiment using a different microphysical scheme. It is found that the temporary active convection, gradually strengthened primary circulation, and a warm core developing at midlevels tend to serve as precursors to RI. The potential vorticity (PV) budget and Sawyer–Eliassen model are utilized to examine the causes and effects of those precursors. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 64 publications
3
28
0
Order By: Relevance
“…Updrafts stronger than 1 m s −1 reached almost 15 km altitude, and a midlevel warm core was centered around 5 km altitude. Such updrafts are known features of an intensifying storm (Rogers et al, ), and a midlevel warm core is a precursor to the RI state (Chang & Wu, ). In contrast, the FO storm kept the same intensity, although mean SST exceeded 29.0°C at all radii within 100 km (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Updrafts stronger than 1 m s −1 reached almost 15 km altitude, and a midlevel warm core was centered around 5 km altitude. Such updrafts are known features of an intensifying storm (Rogers et al, ), and a midlevel warm core is a precursor to the RI state (Chang & Wu, ). In contrast, the FO storm kept the same intensity, although mean SST exceeded 29.0°C at all radii within 100 km (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The evolutions of convective activity and axisymmetrization of the inner core are the features prior to the RI of Typhoon Megi (Chang & Wu, ; Wang & Wang, ). Following Wang and Wang (), we defined the axisymmetricity parameter as the ratio of the azimuthal mean kinetic energy to the total kinetic energy and calculated it for each radial band of 2 km.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, numerical‐model studies (Zhang and Chen, ; Chen and Zhang, ; Wang and Wang, ) have also shown that a sudden increase in deep convection elements (termed convective bursts) occurring inside the RMW may create extra LH, where the high inertial stability constrains this heat to dissipate outside. However, slightly different from these viewpoints emphasizing the importance of deep convection, Chang and Wu () suggested that the LH substantially increases within the mid‐to‐upper troposphere inside the RMW, mostly caused by the weak‐to‐moderate (WM) convection therein, and makes a significant contribution to RI.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical prediction models attempt to take advantage of the fact that a favorable enviroment is a necessity for RI, and forecast RI based on the values of large-scale environmental parameters, such as the vertical wind shear and sea surface temperature (Kaplan et al, 2010;Kaplan & DeMaria, 2003). However, many studies have shown that internal processes may also play an important role in RI, such as the initial intensity of the vortex and inner-core deep convection (e.g., Chang & Wu, 2017;Chen et al, 2017Chen et al, , 2018Rogers et al, 2016;Wang & Wang, 2014;Zagrodnik & Jiang, 2014). Idealized simulations in a no-shear environment suggest that storms with stronger vortices undergo RI earlier (Miyamoto & Takemi, 2015).…”
Section: Introductionmentioning
confidence: 99%